Interaction of milrinone with extracorporeal life support - Whelan, Aviva J.; Mim, Sabiha; Hunt, J. Porter; McKnite, Autumn M.; Green, Danielle J.; Imburgia, Carina E.; Momper, Jeremiah D.; Stitt, Gideon; Watt, Kevin M. (The Journal of extra-corporeal technology, 2024)
Background: Milrinone is commonly prescribed to critically ill patients who need extracorporeal life support such as extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT). Currently, the effect of ECMO and CRRT on the disposition of milrinone is unknown. Methods : Ex vivo ECMO and CRRT circuits were primed with human blood and then dosed with milrinone to study drug extraction by the circuits . Milrinone percent recovery over time was calculated to determine circuit component interaction with milrinone. Results: Milrinone did not exhibit measurable interactions with the ECMO circuit, however, CRRT cleared 99% of milrinone from the experimental circuit within the first 2 hours. Conclusion : Milrinone dosing adjustments are likely required in patients who are supported with CRRT while dosing adjustments for ECMO based on these ex-vivo results are likely unnecessary. These results will help improve the safety and efficacy of milrinone in patients requiring ECMO and CRRT. Due to the limitations of ex-vivo experiments, future studies of milrinone exposure with ECLS should include patient circuit interactions as well as the physiology of critical illness.